(untitled) - Food and Agriculture Organization of the United Nations (Rome, Italy, 2008)
The agrifood transport sector in Latin America and the Caribbean is a key component of the food supply chain, making a significant contribution to gross domestic product in these countries. Well-developed, efficient food transport systems are crucial to the survival of thousands of people, and pivotal to the success or failure of key economic sectors such as agriculture and other major national and international commercial activities. This publication presents a detailed study of problems encountered, covering seventeen countries. The study focuses primarily on stumbling-blocks faced by small farmers, and suggests possible policy and programme interventions to improve the situation in the neediest areas, with repercussions for the population as a whole. (Also published in Spanish)
Keywords: Rural transportation,Economics,Giao thông nông thôn,Kinh tế; Latin America,Châu mỹ La tinh